2004
DOI: 10.1002/em.20002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofHprtmutations in cDNA and genomic DNA of T‐cell mutants from control and 1,3‐butadiene‐exposed male B6C3F1 mice and F344 rats

Abstract: A multiplex PCR procedure for analysis of genomic DNA mutations in the mouse hypoxanthine-guanine phosphoribosyltransferase (Hprt) gene was developed and then used with other established methods for the coincident identification of large- and small-scale genetic alterations in the Hprt gene of mutant T-cell isolates propagated from sham- and 1,3-butadiene (BD)-exposed mice and rats. The spectra data for RT-PCR/cDNA analysis and multiplex PCR of genomic DNA from Hprt mutants were combined, and statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
(71 reference statements)
2
15
0
Order By: Relevance
“…Our results are in agreement with the data from Ma et al (2000) , Burkhart-Schultz and Jones (1997) , and Burkhart-Schultz et al (1996) . Analysis of the in vitro mutational spectra of DEB- and EB-induced mutants in a study by Steen et al (1997a , 1997b) clearly revealed that a decrease in the proportion of single-base substitutions was associated with an increase in the proportion of large deletion mutations Our data and similar findings by Meng et al (2004) indicate that it is not necessary to invoke the formation of DEB as the sole source of large exon deletions; rather, HPRT spectra data from rats indicate that EB-diol is a likely source of deletion mutations.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our results are in agreement with the data from Ma et al (2000) , Burkhart-Schultz and Jones (1997) , and Burkhart-Schultz et al (1996) . Analysis of the in vitro mutational spectra of DEB- and EB-induced mutants in a study by Steen et al (1997a , 1997b) clearly revealed that a decrease in the proportion of single-base substitutions was associated with an increase in the proportion of large deletion mutations Our data and similar findings by Meng et al (2004) indicate that it is not necessary to invoke the formation of DEB as the sole source of large exon deletions; rather, HPRT spectra data from rats indicate that EB-diol is a likely source of deletion mutations.…”
Section: Discussionsupporting
confidence: 78%
“…The authors identified a lower frequency of single-base substitutions, a higher proportion of A:T → T:A transversions and ± 1 frameshift mutations in BD-exposed workers. These changes were also confirmed by Meng et al (2004) in mice and rats. In the future, we plan to analyze more population samples and molecular mutational spectrums in order to elucidate the molecular mutational spectrum associated with butadiene exposure.…”
Section: Discussionsupporting
confidence: 59%
“…Chromosomal alterations (structural and numerical changes) and gene mutations 2-AAF, EO, and DMBA: transgenes (e.g., Lac I); benzene: bone marrow cytogenetics, FISH for translocations, HPRT (in vivo); CPP: bone marrow cytogenetics Chen et al, 2001;Meng et al, 2004;Mittelstaedt et al, 1998;Monroe et al, 1998;Recio et al, 2004;Recio et al, 2001 4. Mutations in critical genes in replicating target cell.…”
Section: Biomarkers Of Exposure and Effect And Bioindicators Of Cancermentioning
confidence: 99%
“…These include alkylated bases, predominantly purines, and interstrand crosslinks Elfarra, 1996, 1999;Tretyakova et al, 1998;Koc et al, 1999;Koivisto et al, 1999;Solomon, 1999;Park and Tretyakova, 2004;Zhang and Elfarra, 2004]. Mutational spectra in cultured cells, as well as mice and humans exposed to BD or BD-epoxides, reveal increases in specific point mutations (A/T?T/A transversions and A/T?G/C transitions) and deletions ranging from simple frameshifts to entire gene regions Recio et al, 2001;Meng et al, 2004]. Studies examining the mutagenicity of synthesized lesions in vitro indicate that *Correspondence to: Jeffrey K. Wickliffe.…”
Section: Introductionmentioning
confidence: 98%